THE USE OF DIGITALIZATION OF INFORMATION IN DEVELOPING DIGITAL MARKETING FOR MSMEs - Rachmawati, Meida (Edusight International Journal of Multidisciplinary Studies, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a central role in economic growth, income distribution, and national stability. Digital marketing is key for MSMEs to promote their products and services, overcome time and distance constraints, and expand market reach. The implementation of digital marketing has a positive impact, enhancing visibility and market reach through website optimization, social media, and SEO strategies. Furthermore, digital marketing significantly contributes to increasing MSMEs' sales through the utilization of social media, e-commerce, and data analysis to understand consumer behavior. However, challenges such as limited resources and a lack of understanding of digital marketing still hinder MSMEs. Therefore, efforts for training and support are needed, along with the design of strategies tailored to the MSME business model to optimize the potential of digital marketing for their business success. In conclusion, the implementation of digital marketing is a strategic step that can provide a positive contribution to the growth and development of MSMEs in this digital era.